Tula virus in populations of small terrestrial mammals in a rural landscape - Heroldová, Marta; Pejcoch, Milan; Bryja, Josef; Jánová, Eva; Suchomel, Josef; Tkadlec, Emil (Vector borne and zoonotic diseases, 2010)
Over 5 years (2000-2004), populations of small mammals from a rural landscape in southern Moravia (Czech Republic) were investigated for the presence of Tula virus (TULV) antigen using the ELISA set Hantagnost. In total, 1566 individuals from 10 species were examined. The prevalence in the common vole (Microtus arvalis Pallas 1778), the main reservoir of TULV, was 10% (n = 871). The prevalence of TULV antigen increases with its population numbers. The highest number of TULV antigen-positive common voles was found in set-aside plots and winter crops, such as rape and winter wheat. All these habitats are important for common vole overwintering. Older and heavier individuals were more often hantavirus antigen positive. From the other small mammal species, 186 pygmy field mice (Apodemus uralensis Pallas, 1811) were examined, of which 3 were positive, which represents the first hantavirus antigen positive record for this species, and of 195 wood mice (Apodemus sylvaticus Linnaeus, 1758) only 1 was positive. The remaining five rodent species (Apodemus flavicollis Melchior, 1834, Mus musculus Linnaeus, 1758, Micromys minutus Pallas, 1771, Myodes glareolus Schreber, 1780, Microtus subterraneus de Sélys-Longchamps, 1836) and two Soricomorpha (Sorex araneus Linnaeus, 1758, Sorex minutus Linnaeus, 1766) were hantavirus antigen negative.
Keywords: Hantavirus; tělesná hmotnost; Rodentia; Shrews; zvířata; rejskovití; mužské pohlaví; Disease Reservoirs; zdroje nemoci; hantavirové infekce; Hantavirus Infections; ženské pohlaví; Animals; Orthohantavirus; nemoci hlodavců; Body Weight; Rodent Diseases; Male; hlodavci; Female